Role of Fluid and Sodium Retention in Experimental Ventilator-Induced Lung Injury - Gattarello, Simone; Pasticci, Iacopo; Busana, Mattia; Lazzari, Stefano; Palermo, Paola; Palumbo, Maria Michela; Romitti, Federica; Steinberg, Irene; Collino, Francesca; Vassalli, Francesco; Langer, Thomas; Moerer, Onnen; et al. (Frontiers in Physiology, 2021)
Background: Ventilator-induced lung injury via respiratory mechanics is deeply interwoven with hemodynamic, kidney and fluid/electrolyte changes. We aimed to assess the role of positive fluid balance in the framework of ventilation-induced lung injury. Methods: Post-hoc analysis of seventy-eight pigs invasively ventilated for 48 hours with mechanical power ranging from 18 to 137 J/min and divided into two groups: high vs. low pleural pressure (10.0±2.8 vs. 4.4±1.5 cmH2O; p<0.01). Respiratory mechanics, hemodynamics, fluid, sodium and osmotic balances, were assessed at 0, 6, 12, 24, 48h. Sodium distribution between intracellular, extracellular and non-osmotic sodium storage compartments was estimated assuming osmotic equilibrium. Lung weight, wet-to-dry ratios of lung, kidney, liver, bowel and muscle were measured at the end of the experiment. Results: High pleural pressure group had significant higher cardiac output (2.96±0.92 vs. 3.41±1.68 L/min; p<0.01), use of norepinephrine/epinephrine (1.76±3.31 vs. 5.79±9.69 mcg/kg; p<0.01) and total fluid infusions (3.06±2.32 vs. 4.04±3.04 L; p<0.01). This hemodynamic status was associated with significantly increased sodium and fluid retention (at 48h respectively: 601.3±334.7 vs. 1073.2±525.9 mmol, p<0.01; and 2.99±2.54 vs. 6.66±3.87 L, p<0.01). Ten percent of the infused sodium was stored in an osmotically inactive compartment. Increasing fluid and sodium retention was positively associated with lung-weight (R2=0.43, p<0.01; R2=0.48, p<0.01) and with wet-to-dry ratio of the lungs (R2=0.14, p<0.01; R2=0.18, p<0.01) and kidneys (R2=0.11, p=0.02; R2=0.12, p=0.01). Conclusions: Increased mechanical power and pleural pressures dictated an increase in hemodynamic support resulting in proportionally increased sodium and fluid retention and pulmonary edema.